The Effect of Profitability, Solvency, and Liquidity on Stock Prices of Logistics and Delivery Subsector Companies Listed on the Indonesia Stock Exchange for the 2020-2024 Period - Siahaan Trinita Tiodora Mardalena; Gusganda Suria Manda; Ariq Farhan Widiyanto; Sandrina Amadya; Desnita Puspitasari (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the effect of profitability (ROA), solvency (DER), and liquidity (CR) on stock prices of logistics and delivery sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research is motivated by the rapid growth of the logistics industry driven by e-commerce expansion and digital transformation, alongside stock price fluctuations influenced by internal financial performance and external economic conditions. This study employs a quantitative approach using purposive sampling, resulting in 12 companies as research samples. Data were analyzed through multiple linear regression analysis using IBM SPSS Statistics to examine both partial and simultaneous effects among the variables. The results reveal that profitability (ROA), solvency (DER), and liquidity (CR) have a positive and significant influence on stock prices, both partially and simultaneously. The coefficient of determination (R²) value of 0.867 indicates that these three independent variables explain 86.7% of stock price variations, while the remaining 13.3% is influenced by other external factors. These findings support the signaling theory and trade-off theory, emphasizing that sound financial performance serves as a positive signal to investors when assessing company prospects. Overall, this study confirms that fundamental analysis based on financial ratios remains a relevant tool for predicting stock market performance, particularly within the logistics and delivery sub-sector that heavily relies on operational efficiency and financial stability.